The adenovirus 55 residue E1A protein is a transcriptional activator and binds the unliganded thyroid hormone receptor - Arulsundaram, Vishnuka D. (Society for General Microbiology, 2014)
The early region 1A (E1A) of human adenovirus types 2 and 5 is differentially spliced to yield five distinct mRNAs that encode different proteins. The smallest E1A RNA transcript encodes a 55 residue (55R) protein that shares only 28 amino acid residues with the other E1A proteins. Even though it is the most abundant E1A transcript at late times post-infection, little is known about the functions of this E1A isoform. In this study, we show that the E1A 55R protein interacts with, and modulates the activity of the unliganded thyroid hormone receptor (TR). We demonstrate that E1A 55R contains a signature motif known as the CoRNR box that confers interaction with the unliganded TR; this motif was originally identified in cellular corepressors. Using a system reconstituted in the yeast Saccharomyces cerevisiae, which lack endogenous TR and TR coregulators, we show that E1A 55R nonetheless differs from cellular corepressors as it functions as a strong co-activator of TR-dependent transcription and that it possesses an intrinsic transcriptional activation domain. These data indicate that the E1A 55R protein functions as a transcriptional regulator.